ANALISIS KOMUNIKASI KRISIS GUBERNUR JAWA TENGAH GANJAR PRANOWO MENGHADAPI PANDEMI COVID-19 - ALKOMARI ALKOMARI (Fakultas Ilmu Komunikasi Universitas Pancasila, 2020)
Central Java Governor Ganjar Pranowo's communication with the public in the midst of the Covid-19 pandemic crisis faced by the public came under the media spotlight. That is because Ganjar Pranowo issued a program to prevent the spread of Covid-19 which is different from other regions. If other regions such as DKI Jakarta, West Java and East Java choose Large-Scale Social Restrictions, Central Java launches Jogo Tonggo. This research focuses on the problem of how the crisis communication is carried out by the Governor of Central Java Ganjar Pranowo in the midst of the Covid-19 pandemic faced by the community. So the aim is to find out how the communication made by Ganjar Pranowo in the midst of the Covid-19 pandemic crisis experienced by people in Central Java. Researchers used descriptive qualitative research methods with constructivist paradigms. While the analysis used to study the research problem is discourse analysis and is supported by the Situational Crisis Communication Theory (SCCT) Theory. The researcher has three research informants including senior journalist who is also the Chairman of Central Java Indonesian Journalists Association Amir Machmud as the main informant, Chairman of RW X Rejosari Urban Semarang City Widyanto Tri Handoko informant supporting one and social media activist Arty Yuniarto as supporting informant two. The results of the study showed that crisis communication conducted by Ganjar Pranowo was very intensive both face-to-face and through online media. The high intensity of communication shows the high concern and closeness of Ganjar Pranowo to the community. The results of the discourse analysis in this study stated that the communication made by the Governor of Central Java Ganjar Pranowo in the midst of the Covid-19 pandemic crisis had political motives for imaging towards the 2024 Presidential Election. This research concludes that crisis communication conducted by Ganjar Pranowo had a positive impact on Ganjar Pranowo's reputation as Governor of Central Java.